Identification, biological characteristics, and screening of control agents against root rot of Ardisia crenata Sims in China - Xiao, Zhien; Guo, Tiantian; Liu, Yuxin; Yuan, Yue; Zhang, Shaotian; Liu, Lu; He, Shiying; Long, Yanling; Yin, Fuqiang; Liu, Ming (Frontiers in Microbiology, 2025)
Ardisia crenata Sims is included in the Chinese Pharmacopoeia and is a valuable traditional medicinal plant. A. crenata Sims root rot was first detected in 2023 in Kaizhou District, Chongqing City, China. This study was undertaken to elucidate the causal pathogen of A. crenata Sims root rot and the biological characteristics of the pathogen and to screen effective pesticides for its management. A pathogenic fungus was isolated and purified from typical lesions on A. crenata Sims, and it was identified using morphological and multi-gene combined analysis. The biological characteristics of the pathogen were investigated using the cross-inoculation method and spore counting technique, while the sensitivity of the pathogen to six chemical pesticides and six biological pesticides was evaluated using the growth rate method. The combination of morphological characteristics and polygenic association identified the pathogenic fungus as Fusarium cugenangense, a member of the F. oxysporum species complex. This is the first report of F. cugenangense causing root rot disease in A. crenata Sims. Among the six tested chemical pesticides, the 500 g/L fluazinam suspension concentrate (SC) showed the best inhibitory effect, with a half-maximal effective concentration (EC50) value of 0.129 μg/mL. Among the six tested biological pesticides, 3% zhongshengmycin soluble liquid (SL) showed the best inhibitory effect, with an EC50 value of 14.474 μg/mL. The conclusion is expected to lay a scientific basis for the diagnosis and control of A. crenata Sims root rot caused by F. cugenangense.